Performance and metabolic responses to a high caffeine dose during prolonged exercise - Graham, T. E.; Spriet, L. L. (Journal of Applied Physiology, 1991)
The present study examined whether a high caffeine dose improved running and cycling performance and altered substrate metabolism in well-trained runners. Seven trained competitive runners [maximal O2 uptake (VO2max) 72.6 +/- 1.5 ml.kg-1.min-1] completed four randomized and double-blind exercise trials at approximately 85% VO2max; two trials running to exhaustion and two trials cycling to exhaustion. Subjects ingested either placebo (PL, 9 mg/kg dextrose) or caffeine (CAF, 9 mg/kg) 1 h before exercise. Endurance times were increased (P less than 0.05) after CAF ingestion during running (PL 49.2 +/- 7.2 min, CAF 71.0 +/- 11.0 min) and cycling (PL 39.2 +/- 6.5 min, CAF 59.3 +/- 9.9 min). Plasma epinephrine concentration [EPI] was increased (P less than 0.05) with CAF before running (0.22 +/- 0.02 vs. 0.44 +/- 0.08 nM) and cycling (0.31 +/- 0.06 vs. 0.45 +/- 0.06 nM). CAF ingestion also increased [EPI] (P less than 0.05) during exercise; PL and CAF values at 15 min were 1.23 +/- 0.13 and 2.51 +/- 0.33 nM for running and 1.24 +/- 0.24 and 2.53 +/- 0.32 nM for cycling. Similar results were obtained at exhaustion. Plasma norepinephrine was unaffected by CAF at rest and during exercise. CAF ingestion also had no effect on respiratory exchange ratio or plasma free fatty acid data at rest or during exercise. Plasma glycerol was elevated (P less than 0.05) by CAF before exercise and at 15 min and exhaustion during running but only at exhaustion during cycling. Urinary [CAF] increased to 8.7 +/- 1.2 and 10.0 +/- 0.8 micrograms/ml after the running and cycling trials.